2018
DOI: 10.1088/1361-6463/aae455
|View full text |Cite
|
Sign up to set email alerts
|

Production of active species in an argon microwave plasma torch

Abstract: In this paper, results from the computational investigation of active species production in an argon microwave plasma torch are presented. We address the main paths of species creation and quenching and focus on their spatial distributions. We show that with the flowing Ar/O2 the radical production is relatively small. The operation of the argon torch can be more effective with an Ar/O2/N2 or Ar/O2/N2/H2O mixture as a feed gas. It was also shown that for high applied voltages the gas temperature inside the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…They contain reactive atomic and molecular species, including unstable, short lived or metastable excited atoms or ions and radicals. Moreover, they prominently contain reactive oxygen species (ROS) such as hydroxyl free radicals (OH) and hydrogen peroxide (H 2 O 2 ), and reactive nitrogen species (RNS) such as nitric oxide (NO) and nitrite (NO 2 − ) [13,14]. The complex nature and exact mechanisms of interaction of atmospheric pressure LTP with biological systems has been intensively investigated [11,[15][16][17][18][19].…”
Section: Background and Motivationmentioning
confidence: 99%
“…They contain reactive atomic and molecular species, including unstable, short lived or metastable excited atoms or ions and radicals. Moreover, they prominently contain reactive oxygen species (ROS) such as hydroxyl free radicals (OH) and hydrogen peroxide (H 2 O 2 ), and reactive nitrogen species (RNS) such as nitric oxide (NO) and nitrite (NO 2 − ) [13,14]. The complex nature and exact mechanisms of interaction of atmospheric pressure LTP with biological systems has been intensively investigated [11,[15][16][17][18][19].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Physical plasma is produced by different types of plasma devices such as the plasma jet [ 3 8 ], dielectric barrier discharge (DBD) [ 9 13 ], floating-electrode dielectric barrier discharge (FE-DBD) [ 14 , 15 ], atmospheric pressure glow discharge torch (APGD-t) [ 16 , 17 ], plasma brush [ 18 ], microhollow cathode discharge air plasma jet [ 19 ], microwave plasma torch [ 20 ], and nanosecond plasma gun [ 21 ]. Plasma jets and DBDs are particularly suitable for biomedical applications as these devices have already entered clinical practice [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, information on the active particles can be obtained through the spectral characteristics. [8,[46][47][48] In this study, the radiation spectrum was measured by the fibre optic spectrometer and shown in Figure 8. Clearly, the plasma jet contains abundant active particles, and their composition and proportion are different in different regions.…”
Section: Active Particle Measurementmentioning
confidence: 99%
“…Thus, Penning ionization is easy to occur on the high-energy quasi-steady He particles at the helium-air micro-mixing interface area. [8,[46][47][48] In this area, plenty of electrons and excited or ionized particles are produced, and intensifying the local collisions. From the spectrum in Figure 8a, it is seen that the He, O, and N 2 + spectral lines have higher intensities at the root zone.…”
Section: Generation and Development Mechanism Of He Plasma Jetmentioning
confidence: 99%